KEANEKARAGAMAN JENIS DAN POLA PENYEBARAN POHON DI HUTAN LINDUNG GUNUNG EGON DUSUN BLIDIT KECAMATAN WAIGETE KABUPATEN SIKKA - Elsanti, Marlina (PT. Hafasy Dwi Nawasena, 2023)
This study aims to determine the diversity of species and distribution patterns of trees in the protected forest of Mount Egon, Blidit Hamlet, Waigete District, Sikka Regency and is expected to be useful for the development of science and technology, especially in the field of forestry and plantations. This research was carried out for one month from February 13 to 13. March 2023. The research used was scientific research using survey and transect methods with an observation plot size of 10 x 10. The results obtained from the study found twelve tree species, namely, Hibiscus tiliaceus, Schleichera oleosa, Santalum Album, Dimocarpus longan, Ficus carica, terminalia catappa toona sinensis, averrhoa bilimbi, canarium indicum, shorea spp, dendrocalamus asper, ficus benjamina, with a diversity index of 2,340 with criteria 1<H'<3, the diversity of tree species in the protected forest of Mount Egon is classified as moderate and the distribution pattern with IM< 1 then the distribution pattern is uniform.